Localization of vasoactive intestinal peptide and toll‐like receptor 2 immunoreactive cells in endostyle of urochordate Styela plicata (Lesueur, 1823). Issue 7 (8th April 2022) - Alesci, Alessio; Pergolizzi, Simona; Lo Cascio, Patrizia; Capillo, Gioele; Lauriano, Eugenia Rita
Abstract: The endostyle is the first component of the ascidian digestive tract, it is shaped like a through and is located in the pharynx's ventral wall. This organ is divided longitudinally into nine zones that are parallel to each other. Each zone's cells are physically and functionally distinct. Support elements are found in zones 1, 3, and 5, while mucoproteins secreting elements related to the filtering function are found in zones 2, 4, and 6. Zones 7, 8, and 9, which are located in the lateral dorsal section of the endostyle, include cells with high iodine and peroxidase concentrations. Immunohistochemical technique using the following antibodies, Toll‐like receptor 2 (TLR‐2) and vasoactive intestinal peptide (VIP), and lectin histochemistry (WGA—wheat‐germagglutinin), were used in this investigation to define immune cells in the endostyle of Styela plicata (Lesueur, 1823). Our results demonstrate the presence of immune cells in the endostyle of S. plicata, highlighting that innate immune mechanisms are highly conserved in the phylogeny of the chordates. Research highlights: Immune cells positive to TLR‐2 and VIP in the endostyle of Styela plicata . Expression of WGA in several zones of endostyle. Use of comparative biology to improve the knowledge about immunology in ascidians. Abstract : From left to right: Styela plicata photographed in its natural environment; morphological staining (May‐Grünwald‐Giemsa) of a section from the endostyle; immunoistochemical localization of VIP and TLR2 in endostyle.